Model Analisis Kebijakan Heuristik, Evaluatif, dan Kritis dalam Pengembangan Kurikulum Pendidikan Agama Islam - Nirmala Hidayati; Hermiati Hermiati; Muhlisin Muhlisin; Muchamad Fauyan (Metta : Jurnal Ilmu Multidisiplin, 2026)
Educational policy analysis in PAI is crucial in the era of globalization to ensure the substance of policies in addressing problems and minimizing the negative impacts of their implementation, while simultaneously ensuring the benefit of stakeholders. This study aims to systematically examine the substance of Islamic education policies by combining Heuristic, Evaluative, and Critical policy analysis frameworks, thereby obtaining recommendations for improving PAI policies that are fairer, more inclusive, and contextual. This study uses a library research method that emphasizes the collection and analysis of data in the form of relevant literature and documents. The results of the analysis indicate that PAI curriculum policies require a comprehensive analytical approach to address educational challenges in the global and digital era. The heuristic model plays a role in uncovering policy issues stemming from the social realities of students and formulating adaptive and contextual policy alternatives. The evaluative model shows that the implementation of PAI policies has a positive impact on improving the quality of learning and strengthening religious values, although their effectiveness is still influenced by the readiness of resources and institutional support. Meanwhile, the critical analysis confirms that PAI policies are inseparable from power relations and the potential for ideological bias. This confirms that the combined model of policy analysis provides a holistic understanding, where Islamic Religious Education policies need to be continued with adjustments to strengthen teacher training and digital infrastructure, and must be reformed to be more include, equitable, and socially transformative by eliminating existing biases, so as to be able to produce a generation of Muslims who are religious, digitally proficient, critical, and highly socially conscious.